PERANSERTA GURU PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DALAM MENINGKATKAN PRESTASI BULUTANGKIS DI KALANGAN SISWA SMP NEGERI 4 SIGLI - Amirzan, Amirzan; Sumarjo, Sumarjo; Yahya, Muhammad; Arifuddin, Arifuddin (Universitas Jabal Ghafur, 2024)
The role of teachers has a significant impact on students' achievements across various sectors, including sports. It is also understood that students' achievements can influence the development of institutions or schools. This study aims to evaluate the contribution of Physical Education, Sports, and Health teachers in enhancing students' badminton skills at SMP Negeri 4 Sigli for the 2024/2025 academic year. This research employs a descriptive quantitative design with a survey approach. The data collection instrument used is a questionnaire with a validity level of 0.830 and a reliability level of 0.915. The study population includes all Education, Sports, and Health teachers, the school principal, the vice principal, classroom teachers, the vice principal for curriculum affairs, and 26 students participating in extracurricular badminton activities. The sample consists of the entire population. The data analysis method used in this study is descriptive with percentages. The findings indicate that the role of Education, Sports, and Health teachers in developing and improving students' achievements at SMP Negeri 4 Sigli is categorized as very good for 7.69% (2 teachers), good for 30.77% (8 teachers), fair for 19.23% (5 teachers), poor for 42.31% (11 teachers), and very poor for 0% (0 teachers).Keywords: Role, Sports Teacher, Achievement, Badminton, Students